Pengembangan Media Pembelajaran Flipbook Untuk Menambah Pemahaman Siswa Pada Materi Keragaman Suku Bangsa Dan Budaya Pada Siswa Kelas V SDN Glonggong 04 Kabupaten Madiun - citra prameswari; Pinkan Amita; Naniek Kusumawati (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This development research has the aim of developing a learning media product in the form of a flipbook to increase students' understanding of the subject of ethnic and cultural diversity in fifth grade students at SDN Glonggong 04 Madiun Regency. This study uses the Borg n Gall development model as a systematic step in the product development process, but the authors use four stages, namely (1) Research and Information Collection (research and data collection), (2) Planning (planning), (3) Develop Preliminary Form Of Product (development of initial product drafts), (4) Preliminary Field Testing (initial field trials). The methods used are documentation, observation, interviews, and questionnaires as data collection instruments. Trials in this development research included material expert validation, media expert validation, linguist validation, class V student responses and also class V teacher responses. the results of the validation assessment from material experts obtained a score of 91% with very valid criteria, the results of the validation assessment media experts obtained a score of 91% with very valid criteria, the results of the validation assessment of linguists obtained a score of 91% with very valid criteria, for class V students' responses obtained a score of 84% with very valid criteria, and for teacher response results obtained a score of 92% with very valid criteria. From the results of the trial it can be concluded that flipbook learning media to increase students' understanding is suitable for use as a learning process.